2015
DOI: 10.1017/s1431927615000239
|View full text |Cite
|
Sign up to set email alerts
|

Design and Application of a Novel In Situ Nano-Manipulation Stage for Transmission Electron Microscopy

Abstract: A novel nano-scale manipulator capable of handling low-dimensional materials with three-dimensional linear motion, gripping action, and push-pull action of the gripper was developed for an in situ experiment in transmission electron microscopy. X-Y-Z positioning and push-pull action were accomplished by a piezotubing system, combined with a specially designed assembly stage that consisted of a lever-action gripping tip backed by a push-pull piezostack. The gripper tip consisted of tungsten wire fabricated by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Such movements could be caused by surface stresses/strains from adsorption of ions in solution onto the crystal surface and/or small motions under the e − beam. Noteworthy is the fact that these bend contours are completely different then pull–push stress/strain tests reported on metal/alloys via in situ TEM measurements 62–64 and that a similar kind of phenomenon but not exactly the same may be observed in the connection of calcite rhombohedra in Nielsen et al 65 (Movie 6 † therein) but not yet noticed/reported until now.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Such movements could be caused by surface stresses/strains from adsorption of ions in solution onto the crystal surface and/or small motions under the e − beam. Noteworthy is the fact that these bend contours are completely different then pull–push stress/strain tests reported on metal/alloys via in situ TEM measurements 62–64 and that a similar kind of phenomenon but not exactly the same may be observed in the connection of calcite rhombohedra in Nielsen et al 65 (Movie 6 † therein) but not yet noticed/reported until now.…”
Section: Resultsmentioning
confidence: 69%
“…Such movements could be caused by surface stresses/strains from adsorption of ions in solution onto the crystal surface and/or small motions under the e À beam. Noteworthy is the fact that these bend contours are completely different then pull-push stress/strain tests reported on metal/alloys via in situ TEM measurements [62][63][64] and that a similar kind of phenomenon but not exactly the same may be observed in the connection of calcite rhombohedra in Nielsen et al 65 (Movie 6 † therein) but not yet noticed/reported until now. From the images and TEM videos, we can infer that several distinct events occur based on the movement of the bend contours: (1) a deposition ("coating") on the surface of the crystal, (2) redistribution of the hypothesized adsorbed particles through some kind of zoning to different regions of the crystal, (3) the repulsion and attraction of one of the zoning bands until reaching a higher concentration zone (i.e.…”
Section: Possible Movement Of Adsorbates On the Surface Of A Fe(iii)-mentioning
confidence: 63%
“…However, the microgrippers designed by Sun et al [26] and Wang et al [27] could not achieve stable gripping. Koo et al [28] designed a single stage asymmetric microgripper based on the principle of lever amplification, which realized the stable gripping of the jaws, but could not be clamped in parallel. Xing et al [29] designed a single stage asymmetric microgripper based on the principle of lever amplification, which realized the parallel gripping of the jaws, but the amplification was small.…”
Section: Introductionmentioning
confidence: 99%